The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.jafc.1c04020
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Peptides: A Promising Alternative to Chemical Preservatives for Food Preservation

Abstract: Bioactive peptides used for food preservation can prolong the shelf life through bacteriostasis and antioxidation. On the one hand, bioactive peptides can inhibit lipid oxidation by scavenging free radicals, interacting with metal ions, and inhibiting lipid peroxidation. On the other hand, bioactive peptides can fundamentally inhibit the growth and reproduction of microorganisms by destroying their cell membranes or targeting intracellular components. Besides, bioactive peptides are biocompatible and biodegrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 147 publications
0
13
0
Order By: Relevance
“…Indeed, previous studies have reported the use of antioxidant protein hydrolysates and/or antioxidant peptides as food preservatives or food additives from various sources, such as fish, soya, eggs, and others [ 15 , 16 ]. Currently, only a few protein hydrolysates and peptides are accepted as food preservatives/additives, including nisin [ 16 ] and pediocin [ 17 ]; however, their use requires specific conditions [ 18 ], as peptides generally have high sensitivity to external environments [ 19 ]. Thus, further studies on protein hydrolysates, including gastrointestinal stability and non-toxicity, are necessary prior to their application as food preservatives or additives [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous studies have reported the use of antioxidant protein hydrolysates and/or antioxidant peptides as food preservatives or food additives from various sources, such as fish, soya, eggs, and others [ 15 , 16 ]. Currently, only a few protein hydrolysates and peptides are accepted as food preservatives/additives, including nisin [ 16 ] and pediocin [ 17 ]; however, their use requires specific conditions [ 18 ], as peptides generally have high sensitivity to external environments [ 19 ]. Thus, further studies on protein hydrolysates, including gastrointestinal stability and non-toxicity, are necessary prior to their application as food preservatives or additives [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Samples were collected; 10 g of each sample was diluted in sterile bags with peptone water (0.2% tween‐20) in a stomacher, and serial dilutions were sown in MRS media and incubated at 35 ± 2°C for 48 hr. We used similar preparations without inoculums as negative controls and 0.1% nisin (Danisco, DuPont, Copenhague, Danemark) as a positive control according to what has been previously described for nisin as an efficient growth controller against LAB (Chung & Hancock, 2000; Gedarawatte et al., 2021; Sozbilen et al., 2018; Zhang et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The main drawbacks of natural plant AMPs include poor chemical stability, astringent flavor, short-term effectiveness, and cytotoxicity. Despite all the negative aspects, plant AMPs can be altered or enhanced for use as food preservatives through chemical synthesis and the addition of delivery techniques such as encapsulation, nanoparticles, or edible packaging [ 48 , 92 ]. With recent developments in technology and scientific advancement, some of the natural plant AMPs have been modified and used in the food industry with improved efficacy ( Table 2 ).…”
Section: Applications Of Plant-derived Amps In the Food Industrymentioning
confidence: 99%